1998
DOI: 10.1161/01.atv.18.9.1470
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Superoxide Anions on Endothelial Ca 2+ Signaling Pathways

Abstract: Abstract-Although the involvement of free radicals in the development of endothelial dysfunction under pathological conditions, like diabetes and hypercholesterolemia, has been proposed frequently, there is limited knowledge as to how superoxide anions (O 2 Ϫ ) might affect endothelial signal transduction. In this study, we investigated the effects of preincubation with the O 2 Ϫ -generating system xanthine oxidase/hypoxanthine (XO/HX) on mechanisms for Ca 2ϩ signaling in cultured porcine aortic endothelial ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 59 publications
0
37
0
Order By: Relevance
“…In the study by Graier et al, 40 enhanced CYP monooxygenase activity was observed in assays with xanthine oxidase/ hypoxanthine. This study therefore suggests exogenous ROS to stimulate CYP monooxygenase activity.…”
Section: Discussionmentioning
confidence: 93%
“…In the study by Graier et al, 40 enhanced CYP monooxygenase activity was observed in assays with xanthine oxidase/ hypoxanthine. This study therefore suggests exogenous ROS to stimulate CYP monooxygenase activity.…”
Section: Discussionmentioning
confidence: 93%
“…-were photometrically measured by the reduction of ferricytochrome C as previously described [10,12]. Confluent SMC were incubated at 37°C in Ca 2+ -free PBS containing 10 µmol/l ferricytochrome C (horse heart type III) with or without SOD (476 U/ml; i.e.…”
Section: Measurement Of Superoxide Anions Omentioning
confidence: 99%
“…Endothelial tyrosine kinase activity was measured by using a customized photometric protein tyrosine kinase kit from Calbiochem-Novabiochem [12,16]. After interaction period cell lysates were obtained by sonification in chilled lysis buffer containing in mmol/l: 20 Tris, 50 NaCl, 1 EDTA, 1 EGTA, 0.2 PMSF, 0.2 mercaptoethanol plus 1 µg/ml pepstatin and 0.5 µg/ml leupeptin (pH 7.4).…”
Section: Measurement Of Superoxide Anions Omentioning
confidence: 99%
“…XO exclusively uses O 2 as the electron acceptor, yielding O 2 2 and hydrogen peroxide (H 2 O 2 ) as reaction by-products. XO is one of the most widely distributed oxidases and has been inculpated in a legion of biological phenomena ranging from H 2 O 2 -mediated signal transduction, through the amplification of inflammatory responses, to organ failure (12,22,53,85).…”
Section: Trypanosome Control In Cape Buffaloes: the Role Of Serum Xanmentioning
confidence: 99%